Prevalence and risk factors for gestational diabetes mellitus according to the Diabetes in Pregnancy Study Group India in comparison to International Association of the Diabetes and Pregnancy Study Groups in El-Minya, Egypt - Ghada M El Sagheer; Lamia Hamdi (SpringerOpen, 2018)
Background The prevalence of gestational diabetes mellitus (GDM) has increased dramatically worldwide in the last decades, but unfortunately it was not studied in Egypt. Objective Assessment of the prevalence of GDM in El-Minya city, Egypt using the Diabetes in Pregnancy Study Group India (DIPSI) in comparison to the International Association of the Diabetes and Pregnancy Study Groups (IADPSG) criteria, and assessment of the risk factors for GDM in this locality. Patients and methods There were 700 pregnant women who underwent the 75 g oral glucose tolerance test irrespective of the meal and plasma glucose measurement after 2 h. In the next morning, fasting and 1 h, and 2 h post-75 g oral glucose tolerance test were assessed. Diagnosis of GDM was carried out according to the DIPSI and IADPSG criteria. Results GDM was diagnosed in 62/700 women (8.86%) by DIPSI versus 52/700 (7.43%) by IADPESG. Compared with IADPSG, the sensitivity and specificity of DIPSI were 100 and 98.5%, respectively, while the positive and negative predictive values were 83 and 100%, respectively. The multiple logistic regression analysis has shown that BMI, urban residency, gestational hypertension, previous history of GDM, gestational hypertension, family history of DM, and the educational level less than secondary school were determined as independent risk factors of GDM. Conclusion The GDM prevalence in El-Minya city was 8.86% by DIPSI versus 7.43% by IADPSG with high sensitivity, specificity, and predictive values. The DIPSI could be considered as a simple, single, convenient, and economical method of GDM screening. However, more evaluation in a bigger patient sample is recommended.